2022
DOI: 10.2519/jospt.2022.11137
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Leisure Time Physical Activity, Weight, and the Onset and Persistence of Nonspecific Neck Pain: A Systematic Review

Abstract: OBJECTIVE: To study the relationships between weight, leisure time physical activity (PA), and the onset and persistence of neck pain in adults with nonspecific neck pain (NSNP). DESIGN: Etiology and prognosis systematic review. LITERATURE SEARCH: Five databases (PubMed, Scopus, Embase, Cochrane Library, PsycINFO) were searched from January 2010 to November 2021. STUDY SELECTION CRITERIA: Case-control or cohort studies assessing the relationship between the onset and the persistence of NSNP, weight, and lei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…28 In addition, a systematic review found there was a lower risk of nonspecific neck pain in those who frequently engage in physical activity. 29 Furthermore, in 2021, a large-scale survey showed that Tehran had one of the lowest levels of physical activity in Iran, while Kohgiluyeh and Boyer-Ahmad was among the highest. 30 Moreover, not engaging in sufficient physical activity was most problematic among adults aged ≥75 years of age in Iran (68.1%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In addition, a systematic review found there was a lower risk of nonspecific neck pain in those who frequently engage in physical activity. 29 Furthermore, in 2021, a large-scale survey showed that Tehran had one of the lowest levels of physical activity in Iran, while Kohgiluyeh and Boyer-Ahmad was among the highest. 30 Moreover, not engaging in sufficient physical activity was most problematic among adults aged ≥75 years of age in Iran (68.1%).…”
Section: Discussionmentioning
confidence: 99%
“…However, an intervention grounded in the health beliefs model resulted in improvements in health‐promoting practices related to neck well‐being among school children in Tehran 28 . In addition, a systematic review found there was a lower risk of nonspecific neck pain in those who frequently engage in physical activity 29 . Furthermore, in 2021, a large‐scale survey showed that Tehran had one of the lowest levels of physical activity in Iran, while Kohgiluyeh and Boyer‐Ahmad was among the highest 30 .…”
Section: Discussionmentioning
confidence: 99%